Humble Leadership and Team Innovation: The Mediating Role of Team Reflexivity and the Moderating Role of Expertise Diversity in Teams - Xinghui Lei (Frontiers in Psychology, 2022)
The current study proposes a moderated mediation model to explain the relationship between humble leadership and team innovation. Our hypothesis integrates social information processing (SIP) theory with the existing literature on humble leadership. As a result, we theorize that when a humble individual leads a team, the team members are more likely to reconsider strategies, review events with self-awareness, share diverse information, and adapt to new ideas, which in turn promotes innovative team activities. Moreover, consistent with the research that emphasizes the inclusion of team culture in exploring leader–innovation relationships, we investigate the moderating role of a team’s expertise diversity in the above positive, indirect relationship. We test our model by using both archival and survey data collected from 135 teams within 18 medium-to-large internet technology firms in China. The findings largely support our theoretical assertions, suggesting that humble leadership has important implications for team processes and innovation.